The Division of Labor, Coordination Costs, and Knowledge - Becker, G. S.; Murphy, K. M. (Quarterly Journal of Economics, 1992)
This paper considers specialization and the division of labor. A more extensive division of labor raises productivity because returns to the time spent on tasks are usually greater to workers who concentrate on a narrower range of skills. The traditional discussion of the division of labor emphasizes the limitations to specialization imposed by the extent of the market. We claim that the degree of specialization is more often determined by other considerations. Especially emphasized are various costs of "coordinating" specialized workers who perform complementary tasks, and the amount of general knowledge available.